The Role of Land Banks in the Customary Land Management Rights of Customary Law Community Units - Nur, Sri Susyanti; Polontoh, Herry M.; Anggraaeni, Andi Evi; Kahar (International Journal of Law and Society, 2025)
Management rights are a form of authority granted by the state to certain parties to manage land. This authority is part of the state's power over land, which is partially transferred to the holder of management rights. Land that can be managed through this right can come from state land or customary land. One of the authorities of Management Rights over state land is the Land Bank, while the Customary Law Community Unity/KMHA provides Management Rights over customary land. Customary Land is a regional property right that is under the governance of the customary law community, whose existence continues to exist but is not bound by certain land rights. These lands can be given Cultivation Rights, Building Rights, and Usage Rights to third parties who cooperate based on the Land Utilization Agreement. Management Rights over state land by the Land Bank have been regulated in the Job Creation Law. However, Management Rights over customary land have not been further regulated after the administration and registration of customary land. This can weaken the existence of KMHA and its customary land because the nature of Management Rights is the right of control from the state so that the land has the status of state land to cooperate with third parties. This research is a normative research, using a legislative and conceptual approach, then analyzed qualitatively and presented descriptively. The results of the study indicate that: Land Banks based on government functions can act as; Dynamizers, Facilitators, and Capacitors in assisting KMHA in managing Customary Land Management Rights. Through land development activities, Land Banks can carry out the function of managing customary land assets. These activities are designed to increase the utilization and use of land that can meet the needs of life and business activities in terms of economics, social, and physical. Thus, Land Banks can later cooperate with third parties to support investment. The mission of the land bank is to secure the availability of land without sacrificing customary land rights for the benefit of the Customary Law Community.